Strategi Dakwah Tokoh Agama Dalam Menanggulangi Perilaku Menyimpang Pada Pemuda Di Desa Serigeni Baru Kecamatan Kayuagung Oki - Rika; Hidayatullah (Social Science and Contemporary Issues Journal, 2023)
This thesis is entitled "Preaching strategies of religious figures in overcoming deviant behavior among youth in Serigeni Baru Village, Kayuagung OKI District". The aim of this research is to find out and analyze the preaching strategies of religious figures in overcoming deviant behavior among youth in Serigeni Baru Village, Kayuagung OKI District and to find out and analyzing the inhibiting and supporting factors of religious figures in dealing with deviant behavior among youth in Serigeni Baru Village, Kayuagung OKI sub-district. This type of research is field research with a qualitative approach. There are two data sources used, namely primary and secondary data sources. Data collection techniques through observation, interviews and documentation. Data analysis technique with three stages, namely data reduction, data presentation, conclusions and verification. Next, we use Al Bayanuni's theory of da'wah strategy and Narwako's theory of deviant behavior. The results of this research show that the da'wah strategy used by religious figures in dealing with deviant behavior in Serigeni Baru Village, Kayuagung OKI District has three da'wah strategies, namely first, the sentimental da'wah strategy, which is a strategy that is implemented through a first approach. Second, the rational strategy, namel by looking at who wants to be given spiritual healing, of course the strategy must bdifferent so that it is more effective and can be put into practice and implemented. Third, the sensory strategy is a strategy that can provide an understanding of religion through an approach to young people and be a good example.